Social Workers’ Experiences of Violence: A Critical Literature Review - Marriette, Natasha C.; Dhungel, Rita (Molung Educational Frontier, 2024)
Violence against social workers is an international issue, yet research worldwide is limited. Social work is a predominantly female profession making violence against social workers an issue of gender-based violence (GBV). Using a post-feminist lens, this paper examines the violence experienced by social workers in the workplace and its impacts on their personal and professional lives. More specifically, the objectives of this study were to 1) critically understand social workers’ experiences of violence in the workplace violence; 2) critically review peer-reviewed and grey literature to examine how intersectionality intersect to escalate the vulnerability of social workers to different forms of GBV; and 3) identify significant gaps and priorities for future policies, practices and research on GBV in the social worker profession. Twenty-four peer-reviewed and grey literature were selected for the study. Three themes emerged through this critical review 1) definition of violence; 2) rates of violence; 3) reporting violence; and 4) impacts of violence. The paucity of research in this area highlights the need for increased research in experiences of violence within the social work workplace, as well as how social work education prepares social work students for the potential of violence within the field of social work.